SELEKSI INDIVIDU HASIL PERSILANGAN TERBUKA PADA TANAMAN UBIJALAR (Ipomoea batatas L.) - Widarsono, Kasianus; Lestari, Sri Umi; Sumiati, Astri (Fakultas Pertanian, 2018)
The purpose of this research is to evaluate and selected genotypes in the halfsib populations obtained from open crosses to the high yield potential with the criteria of ?0.5 kg / plant. This research was conducted in al of Brawijaya university, located Jatikerto Village, Kromengan District, Malang. The research was conducted in May 2016 until September 2016. Five open-ended halfsib families were used in this study, including 73-6/2 OP (62 genotypes), Sukuh OP (56 genotypes), Cilembu OP (67 genotype), Yellow Red OP (57 genotype), and Yellow White OP (56 genotype). The five families were planted on a single 60 cm long Single Row plot arranged in 5 experimental blocks. Each family was placed in 1 experimental block, planted together with five female parent clones, namely 73/6-2, Sukuh, Cilembu, Red Brass, and White Brass. Each parent in each experimental block was planted 10 cuttings. Plants were harvested at the age of 3.5 to 4 months and observed the number of root / tubers, fresh tuber weight (kg/plant), fresh weight of stems (kg / plant),% dry weight of root,% dry weight of stover,/plant), dry weight of stubble (kg/plant), dry weight of biomass (kg/plant) and harvest index. Data analysis based on observation parameters was done using analytical method based on Augmented Randomized Trial Design. The results of this research explain that based on root selection criteria ?0.5 kg/plant of 298 genotypes can be selected 53 genotypes, and 18 genotypes including weight of root ?0.75 kg/plant and 11 genotypes have root weight ?1.00 kg/plant. The halfsib red brass family of OPs has the highest number of selected genotypes of 28 selected genotypes among other halfsib families. The number of genotypes that have the highest yield of root ?0.5 kg/plant is obtained in half family of Red Brass OP, which is 24.56% compared to the other four families of halfsib. The average number of root and the highest root weight was found in the half-family of Red Brass OP ie each of 4.00 bulbs and 0.78 kg of fresh root / plants. Tujuan dari penelitian ini adalah untuk mengevaluasi dan menyeleksi genotipe-genotipe terpilih pada populasi halfsib yang diperoleh dari persilangan terbuka terhadap potensi hasil tinggi dengan kriteria ?0.5 kg/tanaman. Penelitian ini dilaksanakan di Kebun Percobaan Universitas Brawijaya, yang berlokasi di Desa Jatikerto, Kecamatan Kromengan, Kabupaten Malang. Pelaksanaan Penelitian ini dilakukan pada bulan Mei 2016 sampai dengan bulan September 2016. Lima famili halfsib hasil persilngan terbuka digunakan dalam penelitian ini , meliputi 73-6/2 OP ( 62 genotipe), Sukuh OP (56 genotipe), Cilembu OP (67 genotipe), Kuning Merah OP (57 genotipe), dan Kuning Putih OP ( 56 genotipe). Kelima famili tersebut ditanam pada petakan Single Row yang berukuran lebar 60 cm yang disusun dalam 5 blok percobaan. Setiap famili diletakan dalam 1 blok percobaan, ditanam bersama-sama dengan 5 klon induk betinanya, yakni 73/6-2 , Sukuh, Cilembu, Kuningan Merah, dan Kuningan Putih. Masing-masing induk pada setiap blok percobaan ditanam 10 stek. Tanam dipanen pada umur 3,5 sampai 4 bulan dan diamati Jumlah umbi/tanaman, Bobot umbi segar (kg/tanaman), Bobot segar brangkasan (kg/tanaman), % bobot kering umbi, % bobot kering brangkasan, Bobot kering umbi (kg/tanaman), Bobot kering brangkasan (kg/tanaman), Bobot kering biomassa (kg/tanaman) dan Indeks panen. Analisis data berdasarkan parameter pengamatan dikerjakan menggunakan metode analisis berdasarkan Rancangan Percobaan Acak Kelompok Augmented. Hasil penelitian ini menunjukan bahwa berdasarkan kriteria seleksi hasil umbi ?0.5 kg/tanaman dari 298 genotipe dapat dipilih 53 genotipe, dan 18 genotipe diantaranya memiliki bobot umbi ?0.75 kg/tanaman serta 11 genotipe memiliki bobot umbi ?1.00 kg/tanaman. Famili halfsib Kuningan Merah OP memiliki jumlah genotipe terseleksi paling tinggi yakni 28 genotipe terseleksi diantara famili halfsib lainnya. Jumlah genotipe yang memiliki potensi hasil umbi ?0.5 kg/tanaman tertinggi diperoleh pada famili halfsib Kuningan Merah OP, yakni sebesar 24,56% dibandingkan dengan ke empat famili halfsib lainnya. Rerata jumlah umbi dan bobot umbi tertinggi ditemukan pada famili halfsib Kuningan Merah OP yaitu masing-masing sebesar 4,00 umbi dan 0,78 kg umbi segar/tanaman.